KEPRIBADIAN SEORANG DAI - St. Rahmatiah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Dai was the person who conveyed the teachings of Islam to the target of preaching (mad'u). Before preaching, a person should have good preparation in terms of knowledge or ethics. There are several personalities that a person should have that is a spiritual personality that includes personality, attitude and ability. Such qualities as believing in Allah and being righteous, repentant, worshipers, trusting and shidq, grateful, sincere and selfless, friendly and understanding, tawaddu, simple and honest and so on. Whereas such virtues as virtuous, disciplined and wise, polite and competent, are broad-minded and knowledgeable. The physical personality is healthy, the barbecue is good and tidy.